A network approach to overcoming barriers to market engagement for SMEs in energy efficiency initiatives such as the Green Deal. (October 2016) - O'Keeffe, Juliette M.; Gilmour, Daniel; Simpson, Edward
Abstract: The Green Deal (GD) was launched in 2013 by the UK Government as a market-led scheme to encourage uptake of energy efficiency measures in the UK and create green sector jobs. The scheme closed in July 2015 after 30 months due to government concerns over low uptake and industry standards but additional factors potentially contributed to its failure such as poor scheme design and lack of understanding of the customer and supply chain journey. We explore the role of key delivery agents of GD services, specifically SMEs, and we use the LoCal-Net project as a case study to examine the use of networks to identify and reduce barriers to SME market engagement. We find that SMEs experienced multiple barriers to interaction with the GD such as lack of access to information, training, and confusion over delivery of the scheme but benefited from interaction with the network to access information, improve understanding of the scheme, increasing networking opportunities and forming new business models and partnerships to reduce risk. The importance of SMEs as delivery agents and their role in the design of market-led schemes such as the GD are discussed with recommendations for improving SME engagement in green sector initiatives. Highlights: The role of delivery agents should be addressed in voluntary energy reduction schemes. SMEs attempting to engage in the Green Deal market faced multiple barriers. Networks can assist in overcoming SME barriers to entry into new green sector markets. Access to information, contacts and experts are key benefits of business networks. Policy driven market-led schemes must consider all actors to prevent early failures.